Muscle activation in coupled scapulohumeral motions in the high performance tennis serve - Kibler, W. B.; Chandler, T. J.; Shapiro, R.; Conuel, M. (British Journal of Sports Medicine, 2007)
Objective: To evaluate muscle activation patterns in selected scapulohumeral muscles in the tennis serve. These patterns of muscle activation have not been evaluated in other studies of the tennis serve. Fine wire and surface EMG was used to calculate onset and offset timing of muscle activation.